"Hospital at home" care shows similar mortality and subsequent hospital admissions to hospital care for older patients with acutely decompensated chronic heart failure. Issue 1 (23rd February 2010) - Ashby, Sue
Abstract : Commentary on: Tibaldi V Isaia G Scarafiotti C . Hospital at home for elderly patients with acute decompensation of chronic heart failure: a prospective randomized controlled trial . Arch Intern Med 2009 ;169 :1569 –75 .